2023
DOI: 10.21926/obm.genet.2303189
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Transgenic Resistant Plums in Transgrafting Fails to Confer Plum Pox Virus Resistance in Prunus

Abstract: In order to sustain productivity, growers are implementing fruit trees to provide plum pox virus (PPV) resistant varieties. Unfortunately, classical breeding approaches have failed to develop resistant varieties. RNA interference (RNAi) silencing, as an alternate strategy, has been shown to be an efficient approach to combat PPV disease (sharka). PPV resistance based on RNAi has been demonstrated in natural conditions for over 10 years. Experiments using graft inoculation in high-containment greenhouses show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
1
0
0
Order By: Relevance
“…However, scions accumulated specific endogen sRNAs characteristic of the rootstocks ( Sidorova et al., 2021 ). Similar results were found using the PPV-resistant transgenic plums ‘Honeysweet’ or B-14, transformed with the PPV-CP gene ( Ravelonandro and Briard, 2023 ). Conversely, Zhao and Song (2014) showed that PNRSV-hpRNA-derived siRNAs were transmitted up to 1.2 m from the transgenic sweet cherry rootstocks to the non-transgenic scions conferring enhanced PNRSV resistance.…”
Section: Discussionsupporting
confidence: 77%
“…However, scions accumulated specific endogen sRNAs characteristic of the rootstocks ( Sidorova et al., 2021 ). Similar results were found using the PPV-resistant transgenic plums ‘Honeysweet’ or B-14, transformed with the PPV-CP gene ( Ravelonandro and Briard, 2023 ). Conversely, Zhao and Song (2014) showed that PNRSV-hpRNA-derived siRNAs were transmitted up to 1.2 m from the transgenic sweet cherry rootstocks to the non-transgenic scions conferring enhanced PNRSV resistance.…”
Section: Discussionsupporting
confidence: 77%